Integration of Prophetic Leadership Values and Digital Innovation on Formation of Islamic Elementary School Culture - Mutamimah, Duwi Habsari; Mashudi, Kojin; Fuadi, Imam; Tanzeh, Ahmad (Journal of Education Method and Learning Strategy, 2025)
The rapid development of digital technology brings challenges for Islamic educational institutions, including in creating an Islamic school culture that remains relevant in the modern era. In this context, prophetic leadership is key in integrating Islamic values and technology in education. This study aims to analyze the dynamics of prophetic leadership in shaping Islamic school culture and digital technology adaptation at SDIT Darul Falah. The main problem studied is how school principals as prophetic leaders are able to create a strong Islamic culture while implementing digital technology in learning. This study uses a qualitative approach with a case study method. Prophetic leadership at SDIT Darul Falah Sukorejo Ponorogo can form an Islamic school culture that is adaptive to digital technology. Prophetic values such as siddiq, amanah, fathanah, and tabligh are internalized through the collaboration of school principals, teachers, and parents. Technology is used ethically to support Islamic learning, character building, and digital literacy. This approach shows that the digitalization of education can be aligned with Islamic values through transformative and insightful leadership.